2014
DOI: 10.1589/jpts.26.513
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Balance Exercise Program for Enhancement of Gait Function on Temporal and Spatial Gait Parameters in Young People with Intellectual Disabilities

Abstract: [Purpose] The aim of the study was to assess the effect of an 8-week balance exercise program for enhancement of gait function on temporal and spatial parameters of school aged children with intellectual disabilities. [Subjects] Forty young people with intellectual disabilities were assigned either to the balance exercise program for enhancement of gait function group (BG group, n=19) or the control group (n=21). [Methods] The BG group attended an 8-week balance exercise program for enhancement of gait functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 25 publications
(27 reference statements)
1
35
0
1
Order By: Relevance
“…However, a progressive resistance training that was effective in increasing leg strength did not result in an increase in gait speed (Cowley et al 2011). On the contrary, other exercise training programmes (treadmill training, obstacle course training, combined aerobic and resistance training) were found to be effective in improving gait in adolescents and adults with ID both with and without DS (Mendonca et al 2011;Enkelaar et al 2012;Hanegem et al 2013;Lee et al 2014). In addition, in a previous study, we found that the physical fitness components manual dexterity, balance, grip strength, muscular endurance and cardiorespiratory fitness were predictive for a decline in mobility (limitations in walking inside and outside the house) in older adults with ID, over a 3-year period .…”
Section: Introductionmentioning
confidence: 98%
“…However, a progressive resistance training that was effective in increasing leg strength did not result in an increase in gait speed (Cowley et al 2011). On the contrary, other exercise training programmes (treadmill training, obstacle course training, combined aerobic and resistance training) were found to be effective in improving gait in adolescents and adults with ID both with and without DS (Mendonca et al 2011;Enkelaar et al 2012;Hanegem et al 2013;Lee et al 2014). In addition, in a previous study, we found that the physical fitness components manual dexterity, balance, grip strength, muscular endurance and cardiorespiratory fitness were predictive for a decline in mobility (limitations in walking inside and outside the house) in older adults with ID, over a 3-year period .…”
Section: Introductionmentioning
confidence: 98%
“…Based on these findings of this study, when applying Tai Chi therapy to people with intellectual disabilities, it is necessary to provide a program that is designed to show exercise effects by increasing the duration and frequency in order to increase the exercise intensity, and inducing interest to increase concentration. Also, in order to maintain the health status of intellectually disabled people with limited cognitive growth, relatively lower exercise participation rate than that of the general public due to their physical and mental limitations, and significantly reduced physical fitness (Garcia‐Villamisar et al, ; K. J. Lee et al, ), the development of programs that take into account the difficulties in intensive and dynamic physical activities is required, and various supports include health policies should be continuously provided for a long duration, so that they could voluntarily initiate their physical activities. As a policy implication, a government agency may formulate a health policy in which the facilities can introduce exercise programs like Tai Chi therapy for the health of people with intellectual disabilities throughout the country.…”
Section: Discussionmentioning
confidence: 99%
“…Once a person is diagnosed with intellectual disability, he or she will experience difficulties in education, employment, everyday life, and use of convenience facilities due to the limitations in recognition and communication areas (Hardee & Fetters, ; K. Lee, Lee, & Song, ). Most of them are in the medical health‐vulnerable class that needs assistance with daily life because of their limited range of activities as a result of the restrictions on physical activity and mental withdrawal (Kachouri et al, ; K. J. Lee, Lee, Shin, Shin, & Song, ). In 2017, the employment rate of people with disabilities in Korea is 36.5% (Statistics Korea, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations